2020
DOI: 10.1093/bioinformatics/btaa236
|View full text |Cite
|
Sign up to set email alerts
|

MONET: a toolbox integrating top-performing methods for network modularization

Abstract: Summary We define a disease module as a partition of a molecular network whose components are jointly associated with one or several diseases or risk factors thereof. Identification of such modules, across different types of networks, has great potential for elucidating disease mechanisms and establishing new powerful biomarkers. To this end, we launched the ‘Disease Module Identification (DMI) DREAM Challenge’, a community effort to build and evaluate unsupervised molecular network modulariz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Because different network clustering algorithms can produce disparate networks, we tested the robustness of the TMT consensus network generated by the WGCNA algorithm by also generating a co-expression network using an independent algorithm-the MONET M1 algorithm. MONET M1 was identified as one of the top performers in the Disease Module Identification DREAM Challenge and is based on a modularity optimization algorithm rather than the hierarchical clustering approach used in WGCNA 18,19 . We found that all 44 WGCNA modules were highly preserved in the MONET M1 network (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because different network clustering algorithms can produce disparate networks, we tested the robustness of the TMT consensus network generated by the WGCNA algorithm by also generating a co-expression network using an independent algorithm-the MONET M1 algorithm. MONET M1 was identified as one of the top performers in the Disease Module Identification DREAM Challenge and is based on a modularity optimization algorithm rather than the hierarchical clustering approach used in WGCNA 18,19 . We found that all 44 WGCNA modules were highly preserved in the MONET M1 network (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The three top-performing methods from the Disease Module Identification DREAM Challenge were compiled in the MONET toolbox and released to the public for use (https://github.com/BergmannLab/MONET. git) 19 . We selected the M1 method from this toolbox as a complementary network analysis method to explore the AD TMT network.…”
Section: Monet M1 Analysismentioning
confidence: 99%
“…Because different network clustering algorithms can produce disparate networks, we tested the robustness of the TMT consensus network generated by the WGCNA algorithm by also generating a co-expression network using an independent algorithm—the MONET M1 algorithm. MONET M1 was identified as one of the top performers in the Disease Module Identification DREAM challenge, and is based on a modularity optimization algorithm rather than the hierarchical clustering approach used in WGCNA 22, 23 . We found that all 44 WGCNA modules were highly preserved in the MONET M1 network ( Supplementary Figure 2B ), demonstrating the robustness of the TMT consensus network to clustering algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The three top-performing methods from the DMI DREAM Challenge were compiled in the MONET toolbox and released to the public for use (https://github.com/BergmannLab/MONET.git) 23 . We selected the M1 method from this toolbox as a complimentary network analysis method to explore the AD TMT network.…”
Section: Monet M1 Analysismentioning
confidence: 99%
“…This approach has been employed by [ 93 ] to score a set of drugs based on a the similarity of diffusion states between each drug target node-set and COVID-19 target nodes. This methods can be easily implemented using the diffusion state distance (DSD) tool available in the MONET toolbox [ 96 ]…”
Section: Therapeutic Target Identificationmentioning
confidence: 99%